Developing the Intellectual Power of Preschool Children Through Developing Technologies (Eurasian Research Bulletin, 2022)
This article discusses the psychology of preschoolers, the formation of their intellectual and cognitive sphere, the use of technology in intellectual development, its significance and problems. The problem of gifted children in preschool education is investigated, recommendations for the effective development of cognitive and intellectual activity of preschool children are developed.